The practical guide to man-powered bullets : experiments with catapults, musketballs, stonebows, blowpipes, big airguns, bulletbows /: experiments with catapults, musketballs, stonebows, blowpipes, big airguns, bulletbows. (2014) - Middleton, Richard, 1957-
No abstract available